Accelerating Waqf Land Certification in the Digital Era to Achieve Legal Certainty - Farida Hesti Pratiwi; Rini Fidiyani (Universitas Negeri Semarang, 2026)
Waqf land is a religious asset that has a key role function in supporting worship activities and social welfare. However, in practice, there is still a lot waqf land with no official land certificate. In this case, the government issued a policy to accelerate waqf land certification to ensure legal certainty. The government encourages the acceleration of waqf land certification through digital transformation in public services. This article aims to analyze determinants of cause the acceleration of waqf land certification in the digital era and its implementation in achieving legal certainty. This study employs an empirical legal research method with a qualitative approach, through the collection of primary data obtained from interviews and secondary data sourced from laws and regulations and literature studies. The results of the study indicate that in Kebumen Regency, there is still a lot of uncertified waqf land and its implementation is said to be still suboptimal. The factors causing the acceleration of waqf land certification are influenced by several factors, including government regulations and policies, synergy of cooperation between institutions, the active role of officials and assistance to nadzir, increased public legal awareness, and the digitalization of land services. While its implementation demonstrates that actions to accelerate waqf land certification are progressing, strengthening is still need to optimally achieve the set targets. Furthermore, the acceleration of waqf land certification is supported by inter-agency synergy and the use of digital-based information systems.